Social Interaction in Regional Labour Markets - Joerg Lingens; Joerg Heining (European Regional Science Association (ERSA), 2006)
Social interaction, i.e. the interdependence of agents' behaviour via non-market activities, has recently become the focus of economic analysis. Social interaction has been used to explain various labour market outcomes. An important result arising from the literature is the proposition that labour markets are characterised by multiple equilibria. Thus, social interaction is used as an explanation for regional unemployment disparities. Building on this, we construct a Pissarides (2000) type search model with social interaction. Despite social interaction, this type of model is characterised by only one stable equilibrium. Using a unique data set on un-/employment spell data for Germany we analyse whether multiple equilibria in regional labour markets exist. After controlling for structural differences we are able to show that the data supports the assumption of a unique equilibrium. As such, social interaction cannot explain regional unemployment disparities.
Keywords: 330